Learning From the Exceptions: HIV Remission in Post-treatment Controllers - Etemad, Behzad; Esmaeilzadeh, Elmira; Li, Jonathan Z. (Frontiers in Immunology, 2019)
Among the top priorities of the HIV field is the search for therapeutic interventions that can lead to sustained antiretroviral therapy (ART)-free HIV remission. Although the majority of HIV-infected persons will experience rapid viral rebound after ART interruption, there are rare individuals, termed post-treatment controllers (PTCs), who demonstrate sustained virologic suppression for months or years after treatment cessation. These individuals are considered an ideal example of durable HIV control, with direct implications for HIV cure research. However, understanding of the mechanisms behind the capacity of PTCs to control HIV remains incomplete. This is in part due to the scarcity of PTCs identified through any one research center or clinical trial, and in part because of the limited scope of studies that have been performed in these remarkable individuals. In this review, we summarize the results of both clinical and basic research studies of PTCs to date, explore key differences between PTCs and HIV spontaeous controllers, examine potential mechanisms of post-treatment control, and discuss unanswered questions and future research directions in this field.